GENETICS OF RESISTANCE IN KALYANSONA MULTILlNE(S) AGAINST THREE RACES OF YELLOW RUST - G. S. NANDA and S. S. AUJLA, SUDHIR KOCHHAR, K. S. GILL (Indian Phytopathology, 2002)
Genetic information in respect of six wheat lines, their F, s with Agra Local (a universal susceptible variety) and the F, generation in each cross in Kalyansona background against three races of yellow rust is presented. Two different lines with different parentage recorded similar segregation ratio against all the three races. At the same time, one line showed one to three gene segregation for determining resistance against different races. In one of the lines (ML 270), when crossed to Agra Local, a higher order segregation could be operative.